Roles and Responsibilities of Legal Aid Institutions in Trademark Disputes in Indonesia - Dewi, Putri Maha; Sumarna, Dadang; Intizam, Ikhsan; Rahman, Irsan; Nugraha, Agus Bambang (UNIVERSITAS PAKUAN, 2023)
The purpose of this research is to determine the role and responsibilities of legal aid institutions in trademark disputes in Indonesia. The method used is qualitative research, specifically normative legal research. The approach used is a legislative and conceptual approach. The data obtained indirectly from primary, secondary, and tertiary legal materials such as the 2016 Law No. 20, books, and legal research journals. The data collection to solve this problem is done through documentary or library research, using snowball sampling technique, by tracing legal regulations sources in the field of trademarks. After collecting the data, it is analyzed qualitatively. This technique involves studying legal materials or literature to provide an understanding of the research topic and help the writer draw accurate conclusions. The research findings conclude that legal aid institutions (LAI) play a strategic role in assisting individuals or groups, including businesses or other organizations, in resolving legal problems they face. LAIs can provide professional assistance in resolving trademark disputes, making the resolution process easier. In trademark disputes, LAIs can provide advocacy and assistance in the resolution process, including litigation or settlement outside the court. Thus, LAIs can ensure that the rights of parties involved in trademark disputes are protected and fulfilled in a professional and lawful manner.